2017
DOI: 10.3892/mmr.2017.6474
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of human induced pluripotent stem cells in William's E initiation medium supplemented with 3-bromopyruvate and 2-deoxy-d-glucose

Abstract: Hepatocyte selection medium (HSM) is deprived of glucose and supplemented with galactose, and is based on Leibovitz's‑15 (L15) medium. HSM may promote the differentiation of human induced pluripotent stem (iPS) cells towards hepatocyte lineage. These culture conditions result in increased expression of galactokinase (GALK)‑1 and GALK2. However, iPS cells do not survive in HSM. Two potential alternatives to glucose deprivation are treatment with 3‑bromopyruvate (3BP), an analogue of pyruvate, and 2‑deoxy‑d‑gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Previous studies by our group showed that iPS differentiation toward the hepatocyte lineage was promoted in medium without glucose and supplemented with galactose (18,19). Hepatocyte differentiation is promoted by inhibiting glycolysis with 3-bromopyruvate and 2-deoxy-d-glucose, pyruvate and glucose analogs, respectively (29). The current data are consistent with those of the previous studies by our group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies by our group showed that iPS differentiation toward the hepatocyte lineage was promoted in medium without glucose and supplemented with galactose (18,19). Hepatocyte differentiation is promoted by inhibiting glycolysis with 3-bromopyruvate and 2-deoxy-d-glucose, pyruvate and glucose analogs, respectively (29). The current data are consistent with those of the previous studies by our group.…”
Section: Discussionsupporting
confidence: 91%
“…The present RT-qPCR results indicated that AFP and albumin levels were upregulated in cells in HSM with calcium lactate. It was suggested that hepatocyte differentiation was promoted by HSM with lactate, as these two genes are hepatocyte markers (28,29). Previous studies by our group showed that iPS differentiation toward the hepatocyte lineage was promoted in medium without glucose and supplemented with galactose (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the medium played an integral role in establishing a good manufacturing practice (cGMP)compliant process for the manufacturing of hiPSCs that can be used for generating clinically relevant cell types for cell replacement therapy applications [49]. Multiple various modified mediums were proposed, in order to provide a reliable, reproducible and controllable cell culture systems and promote the proliferation and growth of the seeded cells [50][51][52].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Kondo et al found that iPSCs could be converted to high‐purity, differentiated hepatocytes in highly enriched modified medium that contained galactose, phenylalanine, ornithine and oncostatin M, but was deprived of glucose, tyrosine, arginine and pyruvic acid. We have made a list to illustrate the supplements that increase maturity in Table (Kondo et al, ; Tomizawa et al, ; Tomizawa et al, , Tomizawa et al, , Tomizawa et al, , Tomizawa et al, , Tomizawa et al, ) (Table ).…”
Section: Components For In Vitro Modelsmentioning
confidence: 99%